A Guide to Food Selection, Preparation and Preservation - Soriano, Nora Narvaez (Manila, 2010)
A comprehensive guide focusing on the principles and techniques of food selection, preparation, and preservation, tailored to Filipino culinary practices and food safety standards.
Keywords: Food - Handbook, Manuals, Etc